Memory of water - water as a medium of information transfer - Zavrtnik, Saša; Loborec, Jelena; Žubčić, Damir; Sabol, Goran (2020)
Water is one of the five elements that man has been in connection with in a continuous, special and profound way throughout history. By its structure, an angle between atoms, polarity, binding, no doubt it is a fascinating element. Water comes in three aggregate states; it is a universal solvent and, interestingly, a rare substance on Earth whose density is decreased if water temperature is below 4 °C. This is why ice floats on water surface and what makes life possible. Recent very interesting studies have been made that point out the ability of water to store and transfer information. Aquaphotomics studies a so-far unknown world of water in a scientific way. There seems to be an influence on water and its structure through words, music, DNA, etc., via electromagnetic signals. The last four decades gave us an interesting insight through some interesting experiments. This should guide us not just to see the water in its chemical composition, but to see its spatial order of molecules too. Having this knowledge we should examine ourselves, fundamentally, based on the information we share and transmit. All human communication, negative or positive, and human action with and towards water can be reflected in the functioning of the human organism, other living beings, and the ecosystems that they are part of and interfere in.
Bibliografija: 17 jed.
Abstract.
Keywords: Voda -- Struktura -- Memorija vode -- Prijenos informacija